Answer:
See below.
Explanation:
These work just like ordinary algebraic expresssions, except you have to remember always: i^2 = -1 i squared is negative one!
(4 - 3i)(4 + 3i) "FOIL" the expression to get 16 - 3i + 3i - 9i^2. But i^2 = -1, so this is the same as 16 - 3i + 3i + 9. Combine like terms.
Ans. 25
(4 - 3i)(i) Distribute the i to the two terms of the binomial.
4i - 3i^2 = 4i - 3(-1)
Ans. 4i + 3
(6i)(4 + 3i) = (6i)(4) + (6i)(3i) = 24i + 18i^2 = 24i + 18(-1)
Ans. 24i -18
(6i)(i) = 6i^2 = 6(-1)
Ans. -6
(-5)(4 + 3i) = -20 - 15i That's it; there's no i^2 to deal with.
Ans. -20 - 15i
(-5)(i) = -5i Again, that's all there is to it.
Ans. -5i